A Need for Clarity in Animal Welfare Regulation and Research Terminology: What is ‘Cervical Dislocation’ and ‘Stunning’ in On-farm Poultry Slaughter? - Kent, John P.; Salamon , Attila (International Journal of Poultry Science, 2018)
Clarity in the terminology used in animal welfare regulation and science is important. The use of the terms ‘cervical dislocation’ and ‘stunning’ in regulations regarding on-farm poultry slaughter and the role of the scientific evidence in developing these regulations are examined. It is concluded that the use of limited scientific evidence can unwittingly lead to a reduction in animal welfare standards. To avoid such dilemmas, it is suggested that clear definitions in the terminology used is essential at all levels from the design of experiments, the interpretation of results, the work of scientific committees and drafters of legislation and subsequently at the level of the competent authorities and enforcers. If this clarity is not achieved and it has not been achieved in some instances, then confusion and misunderstanding will arise, with negative consequences for animal welfare, primary producers and professionals.